SMU Group’s complex corporate restructuring - Sanchez, Francisco Esteban; Torres, Juan Pablo; Parra, María Francesca; Pavlov de la Fuente, Slavna (Estudios de Administración, 2020)
This case examines the corporate restructuring process of SMU Group, a Chilean retail supermarket chain. The restructuring process was triggered by an internal situation involving operational inefficiencies between the years 2007 and 2012, following an aggressive acquisition process. These problems were the result of an aggressive “Buy-and-Build” strategy, thanks to which by the end of 2012 the Group had grown to become the third largest player in the supermarket industry in Chile. Although this strategy allowed the conglomerate to consolidate its competitive position, it was based on inorganic growth that hid the differences in the operational performance of the different chains and did not allow the Group to take advantage of its own synergies in the process of consolidating the holding company. Around mid-2013, this lack of definition in SMU’s competitive strategy resulted in a serious deterioration of its financial position, due to the significant indebtedness taken on to finance acquisitions, as well as the insufficient generation of cash flow. Furthermore, when compared to the two main players in the industry, SMU showed lower levels of profitability and sales per square meter. To overcome this crisis, SMU implemented a three-year strategic plan (2014-2016), reinforcing three fundamental areas: finance, operations and commercial. The goal was to restore financial viability to the conglomerate by the end of 2016. After executing its plan, SMU achieved an improvement at the operational and commercial levels. However, in the first months of 2017, the risk rating agencies still had doubts about SMU’s future performance and its crisis management capacity. For this reason, Álvaro Saieh, who was serving at the time as Chairman of the Company’s Board of Directors, had several questions: could SMU’s 3-year operational and strategic restructuring plan be considered successful? what are the critical variables that will ensure the sustainability of the company and its growth in the coming years? will I be questioned again like I was in 2013? and finally, what possibilities do I have to create corporate value in the future?